Comic Strip on Students’ Narrative Text Writing Ability - Fauzi, Irvandie Rahmat; Suryanti, Yanti; Vonti, Lungguh Halira (Pedagonal : Jurnal Ilmiah Pendidikan, 2023)
The aim of this research is to prove the effectiveness of comic strips on students' narrative text writing ability. Comic strips are sequential art associated with text with short sequences of images telling short stories. This research applied a pre-experimental method with one group pre-test and post-test design chosen as the research methodology. The eight-grade students in Islamic Middle Schools are taken as the population of this research. Thirty-six students were selected as the samples using the random sampling with the lottery system. The tests were given to measure their narrative writing ability, and the data were analyzed using the t-test formula. From the calculation, the researcher finds the result of the t-test value is 8,49 with the degree of freedom (df) of 35, and the t-table value at the significant level of 0.05 is 2.042. The result shows that the value of the t-test is higher than t-table. It means that the alternative hypothesis (ha) is accepted. Therefore, the researcher concludes that using comic strips positively affects students' ability in writing narrative texts.